Caracteristicas fisicoquimicas y porcentaje relativo de los componentes hidrocarbonados y oxigenados del aceite esencial de las hojas de lantana cámara l. “santa maría” - Namuche Machco, Juan Carlos (2017)
The objective of this research was to determine the physicochemical characteristics and determination of the relative percentage of the oxygenated and hydrocarbon components of the essential oil of the Lantana cámara L. "Santa Maria". The essential oil extraction of Lantana camara was carried out by means of the water vapor trapping method "Hydrodistillation". The performance was determined by the clevenger equipment where 0.4% of the essential oil present in the leaves of Lantana camara L. The organoleptic characteristics were determined (spicy taste, suigeneris odor, transparent yellow color and oily texture); Within the physicochemical parameters were found (density of 0.93880, pH 4, refractive index 1.48868, acid index 3.366); And the solubility was higher with respect to ethanol grade from (70 ° 80 ° 96 ° GL.) And complete in n-hexane and ethyl ether. Finally, the relative percentage of hydrocarbon and oxygen components was determined; obtaining a greater relative percentage in the oxygenated components that was of 24.12%, while the relative percentage in the hydrocarbon components was of 11.55%.